HUBUNGAN SELF-EFFICACY DENGAN KECENDERUNGAN RELAPSE KLIEN RAWAT JALAN DI BADAN NARKOTIKA NASIONAL PROVINSI JAMBI: THE RELATIONSHIP OF SELF-EFFICACY WITH RELAPSE TENDENCY OF OUTPATIENT CLIENTS AT THE NATIONAL NARCOTICS AGENCY OF JAMBI PROVINCE - Bagas Pradana; Siti Raudhoh; Nurul Hafizah (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
ABSTRACT Introduction Drug abuse in Indonesia is increasing rapidly every year. Outpatient clients experience problems from various factors that make them prone to relapse. One factor that influences the tendency to relapse relapse is self-efficacy. Objectives To determine the relationship between self-efficacy and relapse tendency in outpatient clients at the National Narcotics Agency of Jambi Province. Method This study used a quantitative approach with a correlational method. The respondents in this study were 33 outpatient clients of BNNP Jambi with purposive sampling techniques. Data analysis using the Pearson Product Moment correlation test. Results The results of the hypothesis test between the variables self-efficacy and relapse tendency showed a correlation coefficient value of -0.651 with a significant value of 0.000 (p<0.05). This shows that there is a very strong and significant relationship with the direction of the negative relationship between Self-Efficacy and Relapse Tendency, where the higher the Self Efficacy that the individual has, the lower the chance of Relapse Tendency, and vice versa. Conclusion There is a significant negative relationship between self-efficacy and relapse tendency in BNNP Jambi outpatient clients, where the higher the self-efficacy, the lower the tendency to relapse, conversely, the lower the self-efficacy, the higher the tendency to relapse. Keywords : Self-efficacy, Relapse Tendency, Outpatient Client ABSTRAK Pendahuluan Penyalahgunaan napza di Indonesia sangat meningkat pesat setiap tahunnya. klien rawat jalan mengalami permasalahan dari berbagai faktor yang membuat mereka kecenderungan relapse. Salah satu faktor yang mempengaruhi kecenderungan relapse. Tujuan Untuk mengetahui hubungan self-efficacy dengan kecenderungan relapse pada klien rawat jalan di Badan Narkotika Nasional Provinsi Jambi. Metode Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Responden dalam penelitian ini adalah klien rawat jalan BNNP Jambi berjumlah 33 orang dengan teknik pengambilan purposive sampling. Analisis data menggunakan uji korelasi Pearson Product Moment. Hasil Hasil uji hipotesis antara variabel self-efficacy dan Kecenderungan relapse menunjukkan nilai koefisien korelasi sebesar -0,651 dengan nilai signifikan sebesar 0,000 (p<0,05). Hal ini menunjukkan bahwa terdapat hubungan yang sangat kuat dan signifikan dengan arah hubungan negatif antara Self-Efficacy dan Kecenderungan Relapse, dimana semakin tinggi Self Efficacy yang dimiliki individu, maka semakin rendah peluang munculnya Kecenderungan Relapse, dan begitu pula sebaliknya. Kesimpulan Terdapat hubungan negatif signifikan antara self-efficacy dengan kecenderungan relapse pada klien rawat jalan BNNP Jambi, yang mana semakin tinggi self-efficacy, maka semakin rendah kecenderungan relapse, sebaliknya, semakin rendah self-efficacy, maka kecenderungan relapse semakin tinggi. Kata Kunci : Self-Efficacy, Kecenderungan Relapse, Klien Rawat Jalan.